Protection of Traditional Cultural Expressions of the North Sulawesi Community Against Unauthorized Use for Commercial Purposes - Kalalo, Merry Elisabeth; Kapugu, Betsy Anggreni; Rompas, Deizen (Faculty of Law, Universitas Pekalongan, 2025)
This study examines the legal protection of traditional cultural expressions (TCEs) of North Sulawesi communities, which are frequently exploited without authorization for commercial purposes. Such exploitation raises significant legal issues, particularly concerning intellectual property rights violations and the neglect of the collective rights of Indigenous communities. The objective of this research is to analyze the existing legal framework for protecting TCEs and to propose a more adaptive and equitable model of legal protection. This is a normative legal study employing statute, conceptual, and case approaches. Data were analyzed qualitatively and descriptively through literature review and legal document analysis. The novelty of this research lies in its proposed community-based legal protection model that integrates customary law principles with national legislation and international cultural rights standards. The findings reveal that the current legal protections are fragmented and do not yet provide optimal safeguards for Indigenous TCEs. The study recommends the development of a more comprehensive legislative framework, the strengthening of local government roles, and the establishment of protection mechanisms based on the active participation of Indigenous communities